Intestinal microbiota and faecal transplantation as treatment modality for insulin resistance and type 2 diabetes mellitus - Udayappan, S D (Blackwell Science Inc, 2014)
The prevalence of obesity and diabetes mellitus type 2 is increasing rapidly around the globe. Recent insights have generated an entirely new perspective that the intestinal microbiota may play a significant role in the development of these metabolic disorders. Alterations in the intestinal microbiota composition promote systemic inflammation that is a hallmark of obesity and subsequent insulin resistance. Thus, it is important to understand the reciprocal relationship between intestinal microbiota composition and metabolic health in order to eventually prevent disease progression. In this respect, faecal transplantation studies have implicated that butyrate-producing intestinal bacteria are crucial in this process and be considered as key players in regulating diverse signalling cascades associated with human glucose and lipid metabolism.